The fundamental right to good administration in Spanish constitution and in the European Union - Rodríguez-Arana Muñoz, Jaime (Universidad Nacional del Litoral, 2014)
The central role of the citizen in modern constructions of Administrative Law and Public Administration provides the fundamental argument to understand in its full sense the new fundamental right to good administration outlined in the project of European Constitution (Article II-101), according to article 41 of the European Charter of Fundamental Rights. The basis lies in trying to build a more just and humane power which, as a consequence of the right of citizens to appropriate governances and administrations, become suitable instruments to serve objectively the general interest, as determined categorically in article 103 of the Spanish Constitution.